ANALISIS STRATEGI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (PBB) TERHADAP PENINGKATAN TARGET DAN REALISASI PENERIMAANNYA DARI TAHUN 2008-2012 DI KABUPATEN BREBES - , ALVIANITA GUNAWAN PUTRI, Harnanto, Drs., M.Soc.Sc., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to determine how the voting strategies of Land and Building Tax (LBT) conducted by the Department of Revenue and Financial Management (DRFM) in the Brebes District and to determine the level of efficiency and effectiveness of collection of Land and Building Tax (LBT) in the Brebes District from 2008 to 2012 . The type of research use in this paper is descriptive, with research sites in the Brebes District. Brebes District was chosen as the study site , because there are many potential LBT in Brebes untapped perfectly so it will affect the increased acceptance and realization of targets. Types and sources of data used in this study is primary data and secondary data in the form of quantitative time series for 5 (five) years from 2008 to 2012. Analysis data is using quantitative and qualitative methods to analyze the expansion and intensification strategies and of the LBT collection formula by calculates the contribution, efficiency, and effectiveness. The results of this research indicate that the intensification strategy is very active role in optimizing the tax revenue, but the extension strategy can not be implemented associated with the transfer of tax collection LBT became the center of local taxes . Contribution rate showed an average of 23:51 % . Efficiency levels show an average of 9:24 % is considered to be very efficient and effective level of effectiveness is considered to be effective criteria, with the results of calculations which show figures on the percentage of 90-100 % .